The Impact of Digital Finance in G20 Economies on Environmental Protection, Energy Transition Policy, and Technological Innovation - Gulzar, Fatima; Asif, Muhammad; Ibrahim, Maryam; Noor, Manahil (Journal of Environmental and Energy Economics, 2023)
The study investigates the complex relationship between green development and digital finance, first emphasizing China and a subsequent extension to the G20 nations. Using qualitative and quantitative methods to examine provincial data from 2015 to 2023, the research shows how digital money may promote ecologically sustainable development. It highlights the importance of education, economic structure, research and development, and governmental initiatives in boosting the alignment between digital finance and sustainability while identifying regional variations and threshold effects. The interaction of digital finance with technological innovation, environmental protection, and energy transition policy across G20 nations was thoroughly analyzed, providing insightful viewpoints for sustainable development. The study’s quantitative analysis reveals that digital finance has a statistically significant positive impact on technological innovation and environmental sustainability in G20 economies. Empirical results indicate a 0.163% increase in green development for every 1% rise in digital finance adoption. Findings further highlight regional disparities, emphasizing the need for policy-driven financial inclusion strategies. In addition, the study offers practical suggestions for using digital finance to promote technological innovation, environmental preservation, and the creation of energy transition policies within the framework of the G20. Ultimately, the study emphasizes how urgent it is for stakeholders and governments to incorporate digital finance strategies with sustainable development goals, especially in light of international climate agreements, to create a more just, resilient, and ecologically sustainable future.